Adicción al trabajo, compromiso laboral y Burnout en el sector minero industrial - Ferreyros Viza, Ruby Jakelin (2024)
Work is a fundamental activity that influences the well-being, mental health and performance of individuals. In the mining-industrial sector, these dynamics are intensified due to the specific characteristics of the industry. The present research aims to evaluate the predictive impact of Work Addiction and Work Engagement on Burnout Syndrome, as well as to analyze the influence of sociodemographic characteristics. A study was carried out with a sample of 164 participants, 129 men (78.7%) and 35 women (21.3%), aged between 18 and 54 years (M = 34, SD = 7.55) and at least one year of experience in the sector. The instruments used for data collection were the Maslach Burnout Inventory (MBI), the Work Addiction Risk Test (WART) and the Utrecht Work Engagement Scale (UWES-17). A multiple regression analysis was performed to evaluate the predictive relationships between the variables. The results revealed that Work Addiction and educational level are significant predictors of Burnout Syndrome. These findings underline the need to implement strategies that address Work Addiction and promote workplace well-being in the mining-industrial sector.